Two-dimensional ferromagnetic semiconductors of rare-earth monolayer GdX2 (X = Cl, Br, I) with large perpendicular magnetic anisotropy and high Curie temperature. (November 2021) - Liu, Weiqi; Tong, Junwei; Deng, Li; Yang, Bo; Xie, Guangming; Qin, Gaowu; Tian, Fubo; Zhang, Xianmin
Abstract: Two-dimensional (2D) ferromagnetic semiconductors are considered to be one of the most promising candidates for spintronics. Nonetheless, the 2D ferromagnetic semiconductors with large perpendicular magnetic anisotropy and high Curie temperature (Tc ) are rarely reported. Here, through first-principles calculations, we predict a series of ferromagnetic semiconductors monolayer GdX2 (X = Cl, Br, I) by utilizing the rare-earth Gd with large spin-orbit coupling effect. Monte Carlo simulations manifest that the monolayer GdX2 show high Tc beyond 220 K, showing the promising applications in spintronics devices. Most interesting, three monolayer GdX2 show different magnetic anisotropy, among which the easy axis of monolayer GdCl2 is along the [001] direction, while monolayer GdBr2 and GdI2 possess in-plane magnetic anisotropy. Based on the analysis of the contributions from different atomic orbitals to magnetic anisotropy energy (MAE), it is found that the competition between the contributions of Gd- p orbitals, Gd- d orbitals, and p orbitals of halogen atoms to MAE transfers easy axis from out-of-plane to in-plane from Cl to I. The lattice mismatch between 2D materials and substrate definitely affects the properties of 2D materials, −5 % ∼ +5 % strain have been applied on the monolayer GdX2 . The MAE of monolayer GdCl2 can increase from 111 to 190 μeV/f.u. under −5 % compressive strain. Besides, the easy axis of monolayer GdBr2 transfers from in-plane to out-of-plane over −3 % compressive strain. Furthermore, all the monolayer GdX2 have excellent thermal and dynamic stabilities. The present study is useful to design functional 2D materials with large perpendicular magnetic anisotropy and high Tc for the next generation spintronics. Graphical abstract: Image 1 Highlights: Monte Carlo simulations manifest that the rare-earth monolayer GdX2 (X = Cl, Br, I) show a high Tc beyond 220 K. The easy axis of monolayer GdCl2 is along out-of-plane and its MAE is increased up to 190 μeV/f.u. under compressive strain. The strain can manipulate the easy axis directions of monolayer GdCl2 and GdBr2 .